2004
DOI: 10.1249/01.mss.0000113477.11431.59
|View full text |Cite
|
Sign up to set email alerts
|

Passive versus Active Recovery during High-Intensity Intermittent Exercises

Abstract: The longer time to exhaustion for intermittent exercise alternated with passive recovery could be linked to lower metabolic power. As intermittent exercise alternated with passive recovery is characterized by a slower decline in oxyhemoglobin than during intermittent exercise alternated with active recovery at 40% of .VO2max, it may also allow a higher reoxygenation of myoglobin and a higher phosphorylcreatine resynthesis, and thus contribute to a longer time to exhaustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
1
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 36 publications
6
86
1
9
Order By: Relevance
“…Dupont and Berthoin (17) have shown that the AR could be less efficient than the PR to optimize _ VO 2 max, because of the fact that AR enhances blood lactate removal in comparison with PR (13,24,33). Moreover, PR could allow greater reoxygenation of myoglobin and hemoglobin than AR (18,19). The results of this latter study showed that there were no significant differences between AR and PR concerning blood lactate concentration (12.6 6 1 versus 13.1 6 2.7 mmolÁL 21 ), peak HR (183.3 6 13.9 versus 182.5 6 15 bÁmin 21 ) and average HR (66.6 6 11.9; 165.6 6 14.6 bÁmin 21 , respectively).…”
Section: Volume 22 | Number 5 | September 2008 | 1453mentioning
confidence: 99%
“…Dupont and Berthoin (17) have shown that the AR could be less efficient than the PR to optimize _ VO 2 max, because of the fact that AR enhances blood lactate removal in comparison with PR (13,24,33). Moreover, PR could allow greater reoxygenation of myoglobin and hemoglobin than AR (18,19). The results of this latter study showed that there were no significant differences between AR and PR concerning blood lactate concentration (12.6 6 1 versus 13.1 6 2.7 mmolÁL 21 ), peak HR (183.3 6 13.9 versus 182.5 6 15 bÁmin 21 ) and average HR (66.6 6 11.9; 165.6 6 14.6 bÁmin 21 , respectively).…”
Section: Volume 22 | Number 5 | September 2008 | 1453mentioning
confidence: 99%
“…These authors claim that this type of rest break has a beneficial effect on power indicators obtained in subsequent repetitions. In contrast, Dupont et al (2004) show in their study that a 15-second active break (40% VO 2 max) applied after subsequent 15-second efforts (120% VO 2 max) leads to more rapid exhaustion (427 ±118 seconds) than when a 15-second passive break is used. The authors noted that in a test with a passive break the participants performed their work much longer (962 ±314 seconds) (p = 0.001).…”
Section: Discussionmentioning
confidence: 76%
“…It was lower in the test with an active rest break (14.9 ±1.5 W/kg) than in the test with a passive rest break (15.3 ±1.5 W/ kg) p = 0.02. Dupont et al (2004) point out that the use of active breaks (40% VO 2 max) for supramaximal exercise (120% VO 2 max) will cause its working time to be twice as short as when a passive break is used. Our research shows that during the test with an active break the participants did a lot more work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sitting) has not been established either. While it has been suggested that passive recovery allows for resynthesis of substrates like phosphocreatine without incurring the extra metabolic costs that active recovery does [4,28], passive recovery has also been associated with blood flow stagnation and muscle stiffness [25,29].…”
Section: Introductionmentioning
confidence: 99%